Coherencia normativa y lógica deóntica. Comentario a José Juan Moreso, Lo normativo: variedades y variaciones - Navarro, Pablo E. (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This paper analyzes some of the main ideas on logic, rationality, and normativity, defended by José Juan Moreso in the second section of his book Lo normativo: variedades y variaciones. For Moreso, the connection between the existence of norms and acts of promulgation is insufficient to understand the motivational impact of norms, i.e., how they guide human behaviour. For this purpose, it is necessary to take into account the Kantian principle ’ought implies can’, but this principle leads to discarding the existence of incoherent norms (ad impossibilia nemo tenetur). Four possible answers to this challenge of Moreso are analyzed in this article: (i) an abstract conception of norms, independent of the notion of prescription, (ii) the introduction of hierarchical order in the applicable systems, (iii) the rejection of the Kantian principle and (iv) the connection between coherence and hierarchical nature of legal systems.